Protective effect of inulin on thermally treated acerola juice: in vitro bioaccessibility of bioactive compounds. (June 2021) - Fonteles, Thatyane Vidal; Alves Filho, Elenilson de Godoy; Karolina de Araújo Barroso, Maria; de Fátima Dantas Linhares, Maria; Rabelo, Maria Cristiane; Silva, Lorena Mara Alexandre e; Sousa de Brito, Edy; Wurlitzer, Nédio Jair; Rodrigues Pereira, Eliene Penha; Ferreira, Beatriz Manfrinato; Sant'Ana, Anderson de Souza; Rodrigues, Sueli
Abstract: Prebiotic (PREB) and non-PREB acerola juice were subjected to HTST (high-temperature short time) and UHT (ultra-high temperature) processing. A simulated in vitro digestion allowed the bioaccessibility evaluation of the bioactive compounds and the juice composition. NMR and chemometrics were applied to evaluate the changes of processed and non-processed juices. Inulin (IN) had a protective effect in preserving the organic compounds after thermal processing and with the three main stages of in vitro simulated digestion. Both thermal processes increased ethanol, malic acid, choline; fructose; α and β-glucose, and 2-furoic acid (a degradation product of vitamin C) after simulated digestion. For the PREB juices, the addition of IN protected against the pH and the digestive enzymes in acerola juice samples. In thermally processed juices, IN increased vitamin C and total phenolic bioaccessibility. The bioaccessibility of 2-furoic acid increased with the progression of the digestive phases. The presence of IN did not prevent 2-furoic acid formation. However, the amount of these compounds was significantly lower in PREB samples. Thus, thermal processing is a suitable technology for acerola juice preservation, maintaining the vitamin C level despite some formation of 2-furoic acid. Besides a PREB effect, IN also improved the bioactive compounds' bioaccessibility in the treated juice. Graphical abstract: Image 1